The Responsibility of Local Government Towards UMKM Actors, A Case Study of the Curbing of Traders in the Peak Tourist Area - Della Kristina; Yuwono Prianto (Dinasti Research, 2024)
The Puncak tourist area in Bogor is one of the top destinations that attracts thousands of tourists every year. However, this increased tourism activity presents challenges related to public order and spatial management, particularly regarding street vendors who are often perceived as disruptive. The local government enforces vendor regulation to maintain the area's aesthetics and reduce congestion, but this policy often neglects the welfare of MSMEs that depend on trading in the area. This study aims to explore the responsibility of local governments in providing legal protection and support to MSME vendors, especially in the context of vendor regulation policies in the Puncak tourist area. Based on Law No. 23 of 2014 on Regional Government and Law No. 20 of 2008 on MSMEs, the government is obligated to create a conducive business environment and involve the community in policy-making. Findings show that enforcement without alternative solutions harms vendors socially and economically. Local governments need to adopt inclusive and participatory approaches to balance maintaining public order and protecting the welfare of small vendors